Enhanced piezoelectric properties near the morphotropic phase boundary in lead-free (1-x)(Bi0.5K0.5)TiO3-xBi(Ni0.5Ti0.5)O3ceramics - Parkpoom Jarupoom (2018)
© 2015 Elsevier B.V. Lead-free piezoelectric ceramics of the composition (1-x)(Bi0.5K0.50)TiO3-xBi(Ni0.50Ti0.50)O3or (1-x)BKT-xBNiT (when x = 0-0.20 mol fraction) were prepared by a conventional mixed-oxide method and sintered at 1050 °C for 4 h. The effects of BNiT content on the phase equilibria, and the dielectric, ferroelectric and piezoelectric properties were systematically investigated. High density sintered specimens (5.71-6.12 g/cm3) were obtained for all compositions. X-ray diffraction patterns showed that all BKT-BNiT samples exhibited a single perovskite phase which confirms that BNiT and BKT formed a solid solution up to x = 0.20. A morphotropic phase boundary (MPB) separating a BKT-rich tetragonal phase and a BNiT pseudo-cubic phase was identified over the compositional range 0.05 < x < 0.10, where enhanced electrical properties were observed. The optimum dielectric properties (εr= 1710, tanδ = 0.036), ferroelectric properties (Pr= 16.6 μC/cm2, Ec= 22.5 kV/cm and Rsq= 0.86) and piezoelectric properties (d33= 288 pC/N, Smax= 0.22% and d∗33= 313 pm/V) were observed with a relatively high Tm∼ 304 °C within this MPB region. Overall, these results indicate that the BKT-BNiT ceramic system is a promising lead-free piezoelectric candidate for further development for actuator applications.